Association of angiotensin II and receptors in peri-implantation endometrium with microvessel density and pregnancy outcomes of women with recurrent implantation failure after embryo transfer - Qi, Ruofan; Zhang, Tao; Zhang, Yingying; Chung, Jacqueline Pui Wah; Yang, Wen-Jui; Wang, Chi Chiu (Frontiers in Endocrinology, 2023)
Purpose: Whether local angiotensin II (AngII) and their receptors AngII type 1 and 2 receptors (AT1R, AT2R) in endometrium are different and correlate with microvessel density in women with reproductive failure and pregnancy outcomes.Methods: Endometrium during window of implantation from 40 women with recurrent miscarriage (RM) and 40 with recurrent implantation failure (RIF) were compared with 27 fertile women. Peri-implantation endometrium from 54 women prior to euploid embryo-transfer were collected and compared in women with successful pregnancy and unsuccessful pregnancy.Results: Compared with fertile women, expression of AT2R was significantly lower, while AT1R/AT2R expression ratio was significantly higher in stroma of RIF group. Endometrium arteriole MVD was significantly lower and negatively correlated with AT1R/AT2R expression ratio in stroma of RIF group. No significant differences and correlation were found in RM group. Compared with pregnancy group, expression of AT1R and AT2R were significantly lower in all compartments, but only AT1R/AT2R ratio was significantly higher in stroma of non-pregnancy group. Similarly endometrium arteriole MVD was also significantly lower and negatively correlated with AT1R/AT2R ratio in stroma of non-pregnancy group.Local renin-angiotensin system is dysregulated in peri-implantation endometrium and associated with abnormal angiogenesis in RIF and poor implantation outcome after embryo-transfer.